Continuous Aerobic Training in Individualized Intensity Avoids Spontaneous Physical Activity Decline and Improves MCT1 Expression in Oxidative Muscle of Swimming Rats - Scariot, Pedro P. M.; Manchado-Gobatto, Fúlvia de Barros; Torsoni, Adriana S.; dos Reis, Ivan G. M.; Beck, Wladimir R.; Gobatto, Claudio A. (Frontiers in Physiology, 2016)
Although aerobic training has been shown to affect the lactate transport of skeletal muscle, there is no information concerning the effect of continuous aerobic training on spontaneous physical activity (SPA). Because every movement in daily life (i.e. SPA) is generated by skeletal muscle, we think that it is possible that an improvement of SPA could affect the physiological properties of muscle with regard to lactate transport. The aim of this study was to evaluate the effect of 12 weeks of continuous aerobic training in individualized intensity on SPA of rats and their gene expressions of monocarboxylate transporters (MCT) 1 and 4 in soleus (oxidative) and white gastrocnemius (glycolytic) muscles. We also analyzed the effect of continuous aerobic training on aerobic and anaerobic parameters using the lactate minimum test (LMT). 60-day-old rats were randomly divided into three groups: a baseline group in which rats were evaluated prior to initiation of the study; a control group (Co) in which rats were kept without any treatment during 12 weeks; and a chronic exercise group (Tr) in which rats swam for 40min/day, 5 days/week at 80% of anaerobic threshold during 12 weeks. After the experimental period, SPA of rats was measured using a gravimetric method. Rats had their expression of MCTs determined by RT-PCR analysis. In essence, aerobic training is effective in maintaining SPA, but did not prevent the decline of aerobic capacity and anaerobic performance, leading us to propose that the decline of SPA is not fully attributed to a deterioration of physical properties. Changes in SPA were concomitant with changes in MCT1 expression in the soleus muscle of trained rats, suggestive of an additional adaptive response toward increased lactate clearance. This result is in line with our observation showing a better equilibrium on lactate production-remotion during the continuous exercise (LMT). We propose an approach to combat the decline of SPA of rats in their home cages. This new finding is worth for scientists who work with animal models to study the protective effects of exercise.